Znaczenie strategii w dynamicznym otoczeniu - Stańczyk-Hugiet, Ewa (Strategy conception in dynamic world, 2007)
The main aim of the paper is to understand the categories like the conception strategy. The setting of contemporary organizations is dynamic. Therefore, there is necessity to understand the strategy. There are useful evolutionists’ works on the subject, in particular “logical incrementalism” by J. Quinn and the “emergent strategy” conception by H. Mintzberg. Another valuable conception is a concept of ‘dynamic capabilities’ by Teece, Pisano, and Shuen with a reference to the market domination.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 64-75